2016
DOI: 10.1002/da.22543
|View full text |Cite
|
Sign up to set email alerts
|

Disqualified qualifiers: evaluating the utility of the revised DSM-5 definition of potentially traumatic events among area youth following the Boston marathon bombing

Abstract: Background The DSM-5 includes a revised definition of the experiences that qualify as potentially traumatic events. This revised definition now offers a clearer and more exclusive definition of what qualifies as a traumatic exposure, but little is known about the revision’s applicability to youth populations. The present study evaluated the predictive utility of the revised DSM definitional boundaries of traumatic exposure in a sample of youth exposed to the 2013 Boston Marathon bombing and related events. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…There is now considerable evidence from large child samples supporting this current definition of a qualifying traumatic event for diagnosis of PTSD (e.g., Chou et al, 2016). There is also evidence that the current definition of a qualifying traumatic experience for PTSD requires further modification for children under the age of 6 (Chou et al, 2016).…”
Section: Posttraumatic Stress Disordermentioning
confidence: 98%
See 2 more Smart Citations
“…There is now considerable evidence from large child samples supporting this current definition of a qualifying traumatic event for diagnosis of PTSD (e.g., Chou et al, 2016). There is also evidence that the current definition of a qualifying traumatic experience for PTSD requires further modification for children under the age of 6 (Chou et al, 2016).…”
Section: Posttraumatic Stress Disordermentioning
confidence: 98%
“…There is now considerable evidence from large child samples supporting this current definition of a qualifying traumatic event for diagnosis of PTSD (e.g., Chou et al, 2016). There is also evidence that the current definition of a qualifying traumatic experience for PTSD requires further modification for children under the age of 6 (Chou et al, 2016). For example, media-based contact with traumatic events have been associated with PTSD symptoms in many children (Busso et al, 2014;Comer, DeSerisy, & Green, 2016;Comer & Kendall, 2007;Duarte et al, 2011), and it has been suggested that children at early stages of cognitive development may not readily distinguish between televised and real in-person events.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
See 1 more Smart Citation